Environmental conditions of the construction and operation of wind farms “Podborze” near Ostrów Mazowiecka - Brzózka, Milena (Studia Ecologiae et Bioethicae, 2019)
The article presents selected issues related to the construction and operation of wind farms. The case study concerns the planned wind farms “Podborze” near Ostrów Mazowiecka. Potential ranges and effects of the planned investment will be indicated. The last element will be indicating ways to preventive measures and counteracting negative effects.